Evaluating Airline Liability and Compensation in Indonesian Aviation: Mengevaluasi Tanggung Jawab Maskapai Penerbangan dan Kompensasi dalam Penerbangan Indonesia - Atmadja, Rossano Tito; Sudiro, Ahmad (Rechtsidee, 2023)
This study investigates the regulatory framework and legal implications of airline liability in the context of air crash victims' rights in Indonesia, focusing on the enforceability of release and discharge agreements imposed by airlines. The research adopts a normative legal method, employing legislative and conceptual approaches to scrutinize primary and secondary legal materials related to aviation accident compensation. The primary sources include the Indonesian Aviation Act No. 1 of 2009, Article 141, and the Minister of Transportation Regulation PM 41 of 2011, alongside the Warsaw Convention of 1929. Secondary sources comprise academic literature, including books, journals, and research reports. The data were analyzed qualitatively, evaluating the extent to which the concepts of release and discharge align with the prevailing legal principles of transportation liability. The findings reveal that the Indonesian aviation regulations mandate airlines to compensate for deaths, permanent disabilities, or injuries resulting from air accidents, including to the heirs, with a cap set at Rp1.25 billion per passenger. However, the legal strength of release and discharge statements is considered weak, as they are not explicitly regulated, potentially disadvantageous to victims forced to sign as a precondition for compensation, and contrary to consumer protection laws prohibiting the shift of airline responsibilities to consumers. The study recommends a thorough government review of these release and discharge provisions to ensure alignment with national aviation laws, consumer protection statutes, and civil codes, emphasizing fairness and the protection of victims' and heirs' rights. This research contributes to the discourse on aviation liability in Indonesia, highlighting the need for legal reforms to uphold justice and certainty in airline compensation practices.Highlights: Weak Legal Foundation: Release and discharge agreements in Indonesia's aviation sector lack explicit legal backing, undermining their enforceability. Conflict with Consumer Laws: These agreements often contradict consumer protection laws by shifting airline responsibilities to consumers. Need for Legal Reform: There is a pressing need for regulatory review and reform to align compensation practices with fairness and legal standards. Keywords: Aviation Liability, Compensation, Release and Discharge, Consumer Protection, Legal Reform